Sribnian ring structure (Dnieper-Donets depression) — a possible testing ground for the development of the hydrogen potential of the Earth’s interior - Lukin, O.Y.; Shestopalov, V.M. (Reports of the National Academy of Sciences of Ukraine, 2021)
Tectonic-volcanic ring structures correspond to the notion of tube-de-gassing most completely. Endogenic hydrogen is considered as the leading factor of their formation and lithogeodynamic evolution at the both stages “hot” (burning of endogenic hydrogen) and “cold” (ascending migration of “light gases”) phases. Hydrogen, helium, and hybride fields must be connected most of all wit such structures. Among them, megacalderas type with long-term “cold” degassing stage are of the priority of prospecting interest. Sribnian depression (within Dnieper-Donets depression serves as the example of such structures. It is genetically related to the explosion of a volcanic caldera and is characterized by ancient origin (Proterozoic) and long-term geologic evolution on the background of the ascending light gases migration. Intensive hydrogen degassing through the Sribnean ring structure is confirmed by micro- and nano-inclusions in the black-shale domanicoid rocks in the form of particles of native metals (including oxyphile elements — Al, Zn, W, and others) natural alloys and in termetallides — the tracers of ascending flows of deep reduced fluids. The paper deals with comparative cha racteristics of Uzon volcanic caldera (East Kamchatka) and Sribnian ancient volcanic-tectonic ring structure that had special significance in the geological history of the Dnieper-Donets aulacogen. There are all reasons to consider this structure as the exclusive prospecting object for endogenic hydrogen.